Could changing invitation and booking processes help women translate their cervical screening intentions into action? A population-based survey of women’s preferences in Great Britain - Jo Waller; Mairead Ryan; Laura AV Marlow (BMJ Open)
Objectives Many women who do not attend screening intend to go, but do not get around to booking an appointment. Qualitative work suggests that these ‘intenders’ face more practical barriers to screening than women who are up-to-date (‘maintainers’). This study explored practical barriers to booking a screening appointment and preferences for alternative invitation and booking methods that might overcome these barriers.Design A cross-sectional survey was employed.Setting Great Britain.Participants Women aged 25–64, living in Great Britain who intended to be screened but were overdue (‘intenders’, n=255) and women who were up-to-date with screening (‘maintainers’, n=359).Results ‘Intenders’ reported slightly more barriers than ‘maintainers’ overall (mean=1.36 vs 1.06, t=3.03, p<0.01) and were more likely to think they might forget to book an appointment (OR=2.87, 95% CI: 2.01 to 4.09). Over half of women said they would book on a website using a smartphone (62%), a computer (58%) or via an app (52%). Older women and women from lower social grades were less likely to say they would use online booking methods (all ps <0.05). Women who reported two or more barriers were more likely to say they would use online booking than women who reported none (ps <0.01).Conclusions Women who are overdue for screening face practical barriers to booking appointments. Future interventions may assess the efficacy of changing the architecture of the invitation and booking system. This may help women overcome logistical barriers to participation and increase coverage for cervical screening.